Responses of Poultry to Heat Stress and Mitigation Strategies During Summer in Tropical Countries: A Review - AVI, RAHUL (The Iraqi Journal of Veterinary Medicine, 2024)
The poultry industry faces increasing challenges from heat stress caused by global warming, particularly in tropical regions. Heat stress, caused by rising environmental temperatures, undermines the health and productivity of poultry, resulting in significant economic losses. This review comprehensively addresses the physiological and behavioural responses of poultry to heat stress and explores the key mitigation strategies, categorized under genetics, management and feeding. Genetic approaches, like utilizing specific genes in breeding, show promise but require wider adoption. Management practices such as housing design, including orientation, insulation and ventilation, controlled lighting and thermal manipulation are critical to maintaining poultry in their thermoneutral zone. Furthermore, feeding strategies like feed restriction, dual feeding and nutritional manipulation have shown promise in reducing heat stress effects. In addition to feeding strategies, water management is also crucial for mitigating heat stress, especially in tropical areas. Ensuring sufficient water space, maintaining operating waterers, and keeping water cool are essential to encourage adequate drinking. Despite progress, further investigation is required to explore the synergistic effects of combined strategies to improve the resilience of poultry. This review highlights the urgent need for comprehensive approaches to mitigate heat stress in poultry to ensure sustainable productivity under the challenges of global warming